Model Moderasi Beragama Melalui Tradisi Grebeg Suro di Desa Gedangsewu Pare Kediri - Chairudin, Mochamad (Proceedings of Annual Conference for Muslim Scholars, 2023)
This study investigates religious moderation through the Glebeg Suro tradition in Gedanseu, Palle Kediri province. This cultural festival, which is an annual event of various religious groups, is analyzed using an ethnographic approach using field observations and in-depth interviews. Research shows that Grebeg Sulo has emerged as more than just a local cultural festival, but as an example of religious moderation. Participants from different religious backgrounds actively contribute, promoting tolerance and unity in diversity. The results highlighted Grebeg Slough as an effective model of religious moderation within the community.This implication suggests that this book may serve as an inspiration for promoting moderation and interreligious harmony in various regions. This study makes a significant contribution to the literature on the role of local cultural traditions in promoting tolerance and interreligious harmony, while also highlighting the wider applicability of this tradition. Grebeg Suro system outside the local context.